Geniostoma imadae (Loganiaceae), a new single-island endemic species from Kaua‘i, Hawaiian Islands - Kenneth R. Wood; David H. Lorence; Warren L. Wagner; Susan Fawcett (PhytoKeys)
A new endemic species of Geniostoma from Kaua‘i, Hawaiian Islands, is described and illustrated with notes on its distribution, ecology, conservation status, and relationships to other members of the genus. A modification to the existing key for Hawaiian Geniostoma is provided along with a key to all Kaua‘i species. Geniostoma imadae sp. nov., differs from its Hawaiian congeners by its unique combination of glabrous stems, leaves and stipules, flowers 3–10 in open, paniculate cymes with peduncles up to 75 mm long, corolla salverform, lobes 9–11 mm long, calyx lobes 5–9 mm long, and capsules 2-valved with beak 2–4 mm long. Population estimates range from 800 to 1250 individuals distributed across the central northern and eastern windward ridges, slopes and valleys of Kaua‘i. Geniostoma imadae represents a new Vulnerable (VU) single-island endemic species.